Patrimônio arquitetônico e urbano em Porto Alegre: análise da legislação no Centro Histórico (1999-2021) - Riboldi, Bianca Pelicioli (Universidade do Vale do Rio dos Sinos, 2024)
By revisiting urban planning legislation in the city of Porto Alegre, this study aims to analyze the relationship between the preservation of the municipal architectural heritage and this legislation. The main theme developed is the preservation of architectural and urban heritage in Porto Alegre, from the perspective of municipal urban planning legislation from 1999 to 2021. To this end, it proposes an analysis of a Cultural Interest Area located in the city's Historic Center, focusing on a block on Rua dos Andradas. With this study, it is intended to contribute to the preservation of Porto Alegre's architectural heritage. To this end, it analyzes the trajectory of thought on heritage and the relationships between historic centers and their urban evolution. The research has a qualitative approach, encompassing a case study in an area of the historic center. As a result, it aims to propose indicators for the evaluation of current urban legislation and the Porto Alegre Historic Center Rehabilitation Program, which can be applied to other historic centers.
Keywords: Planejamento urbano; Patrimônio arquitetônico; Patrimônio urbano e ambiental; Porto Alegre; Centro histórico; Urban planning; Architectural heritage; Urban and environmental heritage; Historic center; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo